Early feeding after esophageal variceal band ligation in cirrhotics is safe: Randomized controlled trial - Sidhu, Sandeep Singh; Goyal, Omesh; Singh, Saurabh; Kishore, Harsh; Chhina, Rajoo Singh; Sidhu, Samarth Singh (Digestive endoscopy, 2019)
BACKGROUND AND AIM: Oral feeding following variceal ligation in cirrhotics is usually delayed due to fear of rebleeding. Solid diet is usually further delayed (until 72 h) despite lack of evidence. We aimed to compare the impact of early versus delayed feeding on rebleeding following variceal ligation. METHODS: This was a prospective randomized controlled trial including patients undergoing variceal ligation for active esophageal variceal bleeding. Patients were randomized into two groups. In the early-feeding group, liquid diet was given after 1 h following variceal ligation and a regular solid diet was resumed after 4 h. In the delayed-feeding group, patients fasted for the first 4 h after variceal ligation, liquid diet was given until 24 h, soft diet for the next 48 h and a regular solid diet after 72 h. RESULTS: There were 52 and 49 patients in the early and delayed feeding groups, respectively. Very early rebleeding rates [2 (3.84%) vs 1 (2.04%); P ≥ 0.99] and delayed rebleeding rates [2 (3.84%) vs 4 (8.16%); P = 0.75] were similar in both groups. Protein and calorie intake in the early-feeding group was significantly better and early infections in active bleeders were significantly lower compared to the delayed-feeding group. One-month mortality was similar in both groups [3 (5.76%) vs 4 (8.16%); P = 0.75]. CONCLUSION: Early feeding with a regular solid diet in conscious patients after successful variceal ligation for esophageal varices is safe, provides better nutrition and results in lower incidence of infections in bleeders compared to delayed feeding.
Keywords: Randomized Controlled Trials as Topic; Esophageal and Gastric Varices; Ligation; Liver Cirrhosis; ezofageální a žaludeční varixy; endoscopic ligation; rebleeding; jaterní cirhóza; lidé; gastrointestinální krvácení; Gastrointestinal Hemorrhage; kongresy jako téma; Enteral Nutrition; gastrointestinální endoskopie; Gastroenterology; společnosti lékařské; Societies, Medical; Congresses as Topic; gastroenterologie; Endoscopy, Gastrointestinal; enterální výživa; delayed feeding; ligace; randomizované kontrolované studie jako téma; Time-to-Treatment; čas zasáhnout při rozvinutí nemoci; early feeding; cirrhotic; Humans